2017
DOI: 10.25159/0304-615x/2168
|View full text |Cite
|
Sign up to set email alerts
|

Land, Agrarian Reform in Zimbabwe Viewed from a Transformative Social Policy Perspective

Abstract: Much of the scholarly work on Zimbabwe’s land and agrarian reform has largely been premised on the “livelihoods”, “political economy” and the “neo-patrimonial” approaches; much to the neglect of other frameworks. This article attempts to analyse Zimbabwe’s post-2000 land reform experience from a transformative social policy perspective, utilising empirical data obtained from the 2013/14 Sam Moyo African Institute for Agrarian Studies’ six-district-baseline survey. The article argues that although the Fast Trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The labour issue has become prominent and as has been shown in this paper, it has had both negative and positive consequences touching on the generational issues which have been raised. This study has been important to the body of knowledge on the FTLRP as exemplified by the work of Mazwi et al (2018), Chibwana (2016), Chipenda (2019), Tom and Chipenda and Tom (2018) who have argued that the FTLRP, if viewed from a transformative social policy perspective, has enhanced the productive capacities of the beneficiaries such that there are discernible and positive production, social reproduction (emphasis placed here), social protection, redistribution and social cohesion outcomes. From these scholars, emphasis is placed on the social production outcomes of the FTLRP and this paper has shown that indeed there are social reproduction outcomes of the FTLRP which need to be enhanced for the full realisation of the potential of the FTLRP.…”
Section: Discussionmentioning
confidence: 99%
“…The labour issue has become prominent and as has been shown in this paper, it has had both negative and positive consequences touching on the generational issues which have been raised. This study has been important to the body of knowledge on the FTLRP as exemplified by the work of Mazwi et al (2018), Chibwana (2016), Chipenda (2019), Tom and Chipenda and Tom (2018) who have argued that the FTLRP, if viewed from a transformative social policy perspective, has enhanced the productive capacities of the beneficiaries such that there are discernible and positive production, social reproduction (emphasis placed here), social protection, redistribution and social cohesion outcomes. From these scholars, emphasis is placed on the social production outcomes of the FTLRP and this paper has shown that indeed there are social reproduction outcomes of the FTLRP which need to be enhanced for the full realisation of the potential of the FTLRP.…”
Section: Discussionmentioning
confidence: 99%
“…Food systems and food security have been disrupted and threatened since the late 1990s (FAO 2020). This has been due to different factors, such as the disruption of farming activities, destruction and lack of irrigation equipment, limited support to newly resettled farmers, constrained capacity of the state and private sector to support farmers, recurring droughts and drought spells, unfavourable economic climate and hyperinflation, international isolation and the disruption of agricultural value chains (Scoones et al 2011;Mazwi, Chibwana and Muchetu 2017;Waeterloos and Rutherford 2004;Scoones 2016;Tekwa and Adesina 2018).…”
Section: Food Systems and Food Security In Zimbabwe: History And Cont...mentioning
confidence: 99%
“…The newly resettled farmers had to rely on the former large-scale farmers’ second-hand market for tractors services. After the 2000 reform, traditional Western partners not only reduced investments to Zimbabwe (Jones, 2011) but also imposed economic and political sanctions (Mazwi et al, 2017, p. 13; Mukwereza, 2015, p. 3). Zimbabwe explored several avenues to secure funding for agricultural mechanization using budgetary allocations and Reserve Bank of Zimbabwe (RBZ) quasi-fiscal activities, as well as via the import activities of local private companies.…”
Section: Introductionmentioning
confidence: 99%